A Psychological Probe into the Willingness of Physical Fitness Training for Middle School Students in Intensive Physical Training - Wenpu Sun; Yusong Teng; Yichen Bao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
To investigate the impact of psychological treatment on the level of mental and physical exhaustion experienced during intense physical training. This study examined the psychological analysis of physical training in high-intensity physical activity, dividing the two groups into the experimental and control groups using the SAS and SDS self-assessment scales. Randomly chosen 40 healthy male subjects, aged 20±5 years, 175(5±.0) cm in height, and 70±(10) kg in weight, were used in the study. Data processing was carried out using the statistical program SPSS16.0, and measurement data were reported by the mean and standard deviation (x ± S). Following the test, the experimental group's FAI factor score was much lower than that of the control group, and the number of tiredness complaints was also dramatically decreased; The total SAS and SDS scores were lower after the intervention than they were before; following the experiment, FAI factor 1 was associated with the full SAS and SDS scores before the intervention. Three areas of high-intensity physical training show the significance of sports psychology: psychological pre-training, psychological adjustment during high-intensity physical training, and psychological bearing training during high-intensity physical training. The degree and duration of nervous system stimulation during high-intensity physical activity determine how the athlete's psychological endurance under intense load adapts to the burden.